2019
DOI: 10.1186/s42269-018-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro laser radiation induces mutation and growth in Eustoma grandiflorum plant

Abstract: Background: Eustoma grandiflorum is a new floral crop for the international flowers market, moderately coldtolerant annual or biennial plant. A large number of seedlings can be produced by seed propagation but the quality is not uniform due to variations in the flowering time, plant height, and the number of flowers. Propagation of Eustoma grandiflorum plant by tissue culture technique is relatively low. Inducing mutations is one of the powerful tools for breeding biotechnology. Laser mutagenesis is an easy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The multiplication stage plant growth increase in line 8 is accompanied by a significant increase in rooting characteristics and plant photosynthetic pigments. Laser bio-stimulation effects on plant growth were reported on S. chinensis [ 9 ] and eventually quoted by researchers in different plant genera [ 26 , 27 ]. Within the three irradiation periods tested in this study, the 10 min pre-sowing irradiation lines produced the highest growth.…”
Section: Discussionmentioning
confidence: 99%
“…The multiplication stage plant growth increase in line 8 is accompanied by a significant increase in rooting characteristics and plant photosynthetic pigments. Laser bio-stimulation effects on plant growth were reported on S. chinensis [ 9 ] and eventually quoted by researchers in different plant genera [ 26 , 27 ]. Within the three irradiation periods tested in this study, the 10 min pre-sowing irradiation lines produced the highest growth.…”
Section: Discussionmentioning
confidence: 99%
“…The use of different radiation sources has recently made available new choices for rooting in in vitro explant culturing. Many kinds of irradiation, for example, 350-740 nm radiation [20], gammaray [21], and laser [22], have assisted in adventitious root induction and development in various plant species. This method for in vitro rooting without chemical utilization can effectively reduce the cost of the culture medium.…”
Section: In Vitro Persian Violet Root Initiationmentioning
confidence: 99%
“…Since their invention, lasers have been used for many applications; in fact, lasers are a high-tech tool used to meet the challenges of sustainable agriculture [5]. For instance, lasers can be used as biostimulator devices, and studies have shown that laser irradiation can stimulate various plant organs and tissues [6][7][8]. The irradiation of seeds, seedlings or plants by a low-intensity laser can improve their yield and quality due to stimulation of their biochemical and physiological processes [9,10].…”
Section: Introductionmentioning
confidence: 99%